The Double Burden of the COVID-19 Pandemic and Polypharmacy on Geriatric Population – Public Health Implications - Rahman S (Dove Medical Press, 2020)
Sayeeda Rahman,1 Keerti Singh,2 Sameer Dhingra,3 Jaykaran Charan,4 Paras Sharma,5 Salequl Islam,6 Dilshad Jahan,7 Katia Iskandar,8 Nandeeta Samad,9 Mainul Haque10 1School of Medicine, American University of Integrative Sciences, Bridgetown, Barbados; 2Faculty of Medical Science, The University of the West Indies, Cave Hill Campus, Wanstead, Barbados; 3School of Pharmacy, Faculty of Medical Sciences, The University of the West Indies, St. Augustine Campus, Eric Williams Medical Sciences Complex, Mount Hope, Trinidad & Tobago; 4Department of Pharmacology, All India Institute of Medical Sciences, Jodhpur, Rajasthan, India; 5Department of Pharmacognosy, BVM College of Pharmacy, Gwalior, India; 6Department of Microbiology, Jahangirnagar University, Savar, Dhaka 1342, Bangladesh; 7Department of Hematology, Asgar Ali Hospital, Dhaka 1204, Bangladesh; 8School of Pharmacy, Lebanese University, Beirut, Lebanon; 9Department of Public Health, North South University, Bashundhara, Dhaka 1229, Bangladesh; 10The Unit of Pharmacology, Faculty of Medicine and Defence Health Universiti Pertahanan, Nasional Malaysia (National Defence University of Malaysia), Kuala Lumpur, Kem Perdana Sungai Besi, MalaysiaCorrespondence: Mainul HaqueUnit of Pharmacology Faculty of Medicine and Defence Health Universiti Pertahanan, Nasional Malaysia (National Defence University of Malaysia), Kem Perdana Sungai Besi, Kuala Lumpur, 57000, MalaysiaTel +60109265543Email runurono@gmail.comAbstract: COVID-19 pandemic is inducing acute respiratory distress syndrome, multi-organ failure, and eventual death. Respiratory failure is the leading cause of mortality in the elderly population with pre-existing medical conditions. This group is particularly vulnerable to infections due to a declined immune system, comorbidities, geriatric syndrome, and potentially inappropriate polypharmacy. These conditions make the elderly population more susceptible to the harmful effects of medications and the deleterious consequences of infections, including MERS-CoV, SARS-CoV, and SARS-CoV-2. Chronic diseases among elderlies, including respiratory diseases, hypertension, diabetes, and coronary heart diseases, present a significant challenge for healthcare professionals. To comply with the clinical guidelines, the practitioner may prescribe a complex medication regimen that adds up to the burden of pre-existing treatment, potentially inducing adverse drug reactions and leading to harmful side-effects. Consequently, the geriatric population is at increased risk of falls, frailty, and dependence that enhances their susceptibility to morbidity and mortality due to SARS-CoV-2 respiratory syndrome, particularly interstitial pneumonia. The major challenge resides in the detection of infection that may present as atypical manifestations in this age group. Healthy aging can be possible with adequate preventive measures and appropriate medication regimen and follow-up. Adherence to the guidelines and recommendations of WHO, CDC, and other national/regional/international agencies can reduce the risks of SARS-CoV-2 infection. Better training programs are needed to enhance the skill of health care professionals and patient’s caregivers. This review explains the public health implications associated with polypharmacy on the geriatric population with pre-existing co-morbidities during the COVID-19 pandemic.Keywords: elderly, COVID-19, pandemic, viral infection, polypharmacy, co-morbidity, public health